The fiscal theory of the price level in a world of low interest rates - Marco Bassetto; Wei Cui (Federal Reserve Bank of Chicago, 2017)
A central equation for the fiscal theory of the price level (FTPL) is the government budget constraint (or "government valuation equation"), which equates the real value of government debt to the present value of fiscal surpluses. In the past decade, the governments of most developed economies have paid very low interest rates, and there are many other periods in the past in which this has been the case. In this paper, we revisit the implications of the FTPL in a world where the rate of return on government debt may be below the growth rate of the economy, considering different sources for the low returns: dynamic inefficiency, the liquidity premium of government debt, or its favorable risk profile.
Keywords: 330; Finanzpolitik; Inflationsrate; Preisniveau; Öffentliche Schulden; Zins; Risikoprämie; Theorie